Spatial Predictive Modeling of Fish Distributions Incorporating Habitat Utilization and Behavior in the Context of Marine Protection - Stamoulis, Kostantinos (Curtin University, 2018)
This research focused on improving species distribution models (SDMs) of targeted reef fishes by incorporating fish behavior. Results show that 1) fishing patterns are critical inputs for SDMs, 2) fish wariness provides a proxy for spear fishing pressure, and 3) accuracy of SDMs increase when fish wariness is included as a predictor of targeted fish biomass. Fish wariness could be used to refine measures of fish assemblages and SDMs, improving management of coastal fisheries.